PERNIKAHAN DI BAWAH UMUR DI KALANGAN MASYARAKAT MUSLIM SUKU BAJO - Zulkifly; Kurniati; Kiljamilawati (Universitas Islam Negeri Alauddin Makassar, 2024)
This study discusses underage marriage among the Bajo Tribe Muslim Community (Case Study in Alok Barat District, Sikka Regency, Flores, East Nusa Tenggara). Therefore, the author finally explored how the views of the community and the impact of underage marriage among the Bajo Tribe Muslim Community in Alok Barat District, Sikka Regency, Flores, East Nusa Tenggara. The type of research used is field research, in which the main source of this research is data in the field such as the results of observations and interviews. The results of this study reveal that underage marriages are still rife in the Bajo Tribe, Alok Barat District, Sikka Flores Regency, East Nusa Tenggara due to a lack of understanding of the legal age limit for marriage. Social, educational, and economic factors also influence someone to enter into underage marriages. The positive impact of underage marriage is to prevent adultery which is prohibited by Allah SWT, but there are also negative impacts such as the risk of death for mothers and babies during childbirth, disharmony in marriage and divorce, and the invalidity of the law if there is no dispensation for marriage from the religious court.